Draft Genome Sequences of Two Cyanobacteria Leptolyngbya spp. Isolated from Microbial Mats in Miravalles Thermal Spring, Costa Rica - Brenes Guillén, Laura Natalia (2021)
We report the draft genome sequences of Leptolyngbya sp. strain 7M and Leptolyngbya sp. strain 15MV, isolated from Miravalles Thermal Spring, Costa Rica. The thermophilic cyanobacteria exhibit unique diversity features that provide insight into the adaptation and evolution of phototrophic microorganisms in geothermal habitats.